GENESIS OF RINGWOODITE DURING METAMORPHISM INDUCED BY IMPACT WAVES: EXPERIMENTAL DATA - Sazonova L.V.; Fel'dman V.I.; Kozlov E.A.; Dubrovinskaya N.A.; Dubrovinskii L.S. (My University, 2006)
Ringwoodite, a high-density olivine modification, was first synthesized by loading plagioclase-biotite-quartz schist containing garnet and staurolite by impact waves. Ringwoodite was identified in the impact-thermal aggregates that replaced biotite (together with a mineral corresponding to spinel in chemical composition and with a biotite residue). The physical parameters under which ringwoodite was synthesized in this experiment (Pimp ~ 20-30 GPa and T ~ 1060-1500°C) include a pressure approximately 1.5 times higher than that in static analogous experiments. The ringwoodite was formed via the regrouping of and the associated removal and addition of material, as follows from the development of ringwoodite after biotite, a mineral of principally different composition. Component migration was reliably confirmed by the microprobe mapping of the chemistries of the original and newly formed minerals, which makes the origin of the ringwoodite similar to the origin of diamond (togorite) in the Kara astrobleme, where the impact loading was up to ten times higher than the static pressure. © Pleiades Publishing, Inc. 2006.